Control of Clubroot Plasmodiophora brassicae Wor. With Dry Formulation of Trichoderma sp. On Broccoli Plants (Brassica oleracea L.) - Nuraini, Yusi; Rahman, Abdul; Novatiano, Chesara (Biotik, 2026)
One of the common diseases in broccoli plants is clubroot caused by soil-borne pathogens (Plasmodiophora brassicae Wor.). One form of prevention of this disease is by applying dry formulation of Trichoderma sp. This study aims to determine the effect of giving dry formulation of Trichoderma sp. in controlling clubroot disease in Broccoli. This study used a Randomized Block Design (RBD) with 4 treatments, namely P0 (0 grams/liter), P1 (5 grams/liter.), P2 (7 grams/liter), and P3 (9 grams/liter) with 6 replications per treatment. The results showed that P3 was the most effective in increasing plant height, leaf blades, leaf length, leaf width, wet weight, and broccoli flower weight. While P2 was the most effective concentration in controlling clubroot disease with the lowest disease severity level of 23.85. Keyword: Dry Formulation; Trichoerma sp.; Broccoli; Mace Root.